Prediction of 2000 metre rowing performance in single scullers using indices of aerobic and anaerobic power - Jürimäe, J.; Jürimäe, T.; Mäestu, J.; Pihl, E. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
The purposes of this study were to: 1) examine the relationships between rowing performance and indices of metabolic parameters; and 2) determine the best predictive indices of rowing performance. Ten male rowers (18.90± 1.66 yrs; 186.20± 6.25 cm; 79.27± 7.30 kg; %body fat: 10.49± 2.30%) were subjected to four exercise sessions on a rowing ergometer (Concept II, Morrisville, USA). An incremental exercise test to determine the maximal oxygen uptake (VO2max), the corresponding maximal aerobic power (Pamax) and anaerobic threshold (AT4), a 2000 metre "all-out" test to determine the performance parameters (P2000), a five maximal strokes to determine the maximal alactic anaerobic power (P5), a 40 seconds "all-out" test to determine the maximal lactic anaerobic power (P40), and a 95% Pamax test until volitional exhaustion to determine the maximal aerobic power were performed. In addition, competition results in 2000 metre race on single sculls were obtained. Mean VO2max was 4.854± 0.631 l.min-1 (61.61± 5.59 ml.min.-1kg-1) and AT4 274.80± 40.70 W, which corresponded to 74.20± 4.20% of Pamax. P2000 sustained by the rowers was 358.40± 51.46 W, which corresponded to 96.71± 4.70% of their Pamax. While the subjects rowed at a mean overall work rate of 347.05± 34.43 W during the 95% Pamax test. Mean competition time on 2000 metre distance on single sculls was 448.2± 13.1 sec (7 min 28 sec), heart rate 179.94± 4.92 beats.min-1 and blood lactate 16.02± 2.42 mmol.l-1. Forward stepwise multiple regression analysis produced the following model to predict 2000 metre rowing performance on single sculls when using all measured parameters of anaerobic metabolism as dependent variables: Time (sec)=518.87-0.13(P5) (R2=0.516). Using parameters of aerobic metabolism, the following model was presented: Time (sec)=512.49-0.08(AT4)-8.46(VO2max) (R2=0.646). In conclusion, the competition results in 2000 metre distance on single sculls are dependent on the level of anaerobic alactic power (P5), and submaximal (AT4) and maximal (VO2max) aerobic power. The findings of our study support the hypothesis that competitive rowing may be classified as a "power (anaerobic) - endurance (aerobic)" event.